Community Perception of Smoke-Free Policy in Depok City, Indonesia - Krisna Puji Rahmayanti; Arfah Habib Saragih; Murwendah Murwendah (Soshum: Jurnal Sosial dan Humaniora, 2019)
This study aims to analyze the perception of the targeted group to the smoke-free policy as part of university community service. Several studies have supported that smoke-free policy is a useful tool to reduce the smoke prevalence and minimize risk factor of the cigarette consumption. Depok City in West Java, Indonesia, is a city that has started the implementation of smoke-free policy since 2015 but this city still deals with critiques about the weakness of the process. This study is a qualitative research. This perception of the targeted group will become a baseline for the further step of the collaborative governance research. This study conducted one focus group discussion which involved 28 community members as informants. The result found that majority of the informants already know about the harmful impact of smoking, but some of them do not understand the existence of the smoke-free policy. Smoke-free policy in Depok City gives the essential duty to the citizen to conduct monitoring and evaluation of the implementation stage. However, this study found that the informants do not well informed about this role and difficult to identify available channels for monitoring. Therefore, this study proposes to Depok City government to build information and communication platform to send and receive message from and to the people related to the monitoring and evaluation of the smoke-free policy. As technology develops, there are many mechanisms to share the information and communicate with people or organization which may increase the beneficial interaction between people and the government of Depok City. This communication channel is very significant to align the community perception or the people perspective with the policymaker's point of view.